Determinants of Stock Volatility: Trading Volume, Profitability, Earnings Volatility, and Book-to-Market Ratio - Amelia Nurlaeli Hidayah; Usman Usman; Agus Prayitno; Ana Kadarningsih (Celebes Scholar pg, 2026)
This study aims to analyze the effect of Trading Volume, Profitability, Earnings Volatility, and Book-to-Market Ratio on stock price volatility of technology sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research is motivated by the high level of stock price fluctuations in the rapidly growing technology sector, which is accompanied by considerable market uncertainty. This study employs a quantitative explanatory approach using secondary data obtained from financial statements and stock trading records. The sample was selected using a purposive sampling method based on data availability and consistency throughout the observation period. Panel data regression analysis was applied to examine the impact of the independent variables on stock price volatility. The results indicate that trading volume has a significant negative effect on stock price volatility, suggesting that higher market liquidity contributes to price stability. Profitability does not have a significant effect on stock price volatility, indicating that earnings information is largely anticipated by investors and does not trigger substantial market reactions. Earnings volatility has a significant positive effect on stock price volatility, implying that unstable earnings increase perceived risk and market uncertainty. Furthermore, the book-to-market ratio has a significant positive effect on stock price volatility, reflecting that firms with higher fundamental risk tend to experience greater price fluctuations.